Biomedical ethics and clinical oversight in multisite observational neuroimaging studies with children and adolescents: The ABCD experience. (August 2018) - Clark, Duncan B.; Fisher, Celia B.; Bookheimer, Susan; Brown, Sandra A.; Evans, John H.; Hopfer, Christian; Hudziak, James; Montoya, Ivan; Murray, Margaret; Pfefferbaum, Adolf; Yurgelun-Todd, Deborah
Abstract: Observational neuroimaging studies with children and adolescents may identify neurological anomalies and other clinically relevant findings. Planning for the management of this information involves ethical considerations that may influence informed consent, confidentiality, and communication with participants about assessment results. Biomedical ethics principles include respect for autonomy, beneficence, non-maleficence, and justice. Each project presents unique challenges. The Adolescent Brain and Cognitive Development study (ABCD) collaborators have systematically developed recommendations with written guidelines for identifying and responding to potential risks that adhere to biomedical ethics principles. To illustrate, we will review the ABCD approach to three areas: (1) hazardous substance use; (2) neurological anomalies; and (3) imminent potential for self-harm or harm to others. Each ABCD site is responsible for implementing procedures consistent with these guidelines in accordance with their Institutional Review Board approved protocols, state regulations, and local resources. To assure that each site has related plans and resources in place, site emergency procedures manuals have been developed, documented and reviewed for adherence to ABCD guidelines. This article will describe the principles and process used to develop these ABCD bioethics and medical oversight guidelines, the concerns and options considered, and the resulting approaches advised to sites.